THE EFFECT OF THE IMPLEMENTATION OF THE COMPENSATION SYSTEM ON EMPLOYEE WORK MOTIVATION AT PT. XYZ WHICH IS ENGAGED IN THE MANUFACTURING INDUSTRY IN THE TANGERANG REGENCY AREA - Ichsan Prastya Firmansyah; Aip Sarifudin; Mira Apriana Markus; Fathimah Az-zahra; Haniyyah Haniyyah; Saefullah Saefullah; Vina Afianti; Winanti Winanti; Akhmad Farhan (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2026)
The manufacturing industry in Tangerang Regency faces significant challenges in maintaining and increasing labor productivity, where employee motivation is a crucial factor influenced by various aspects of wage and benefits policies. This study uses a quantitative method by distributing questionnaires to 100 employee participants. This study applied a saturated sampling technique, so that the entire population was used as a sample, and data analysis was carried out using multiple linear regression with the support of SPSS software. The results of the analysis showed that the compensation system had a positive impact and had a significant influence on work morale, with a determination effect (R²) of 0.684. This situation shows that 68.4% of the difference in work motivation is influenced by compensation factors. This study recommends that companies consider the compensation system as a strategic instrument in improving staff morale.